Penerapan Metode Pembelajaran di MI Terpadu Al-Ma’shum Surakarta - Kinesti, Rakanita Dyah Ayu; Syifa, Chilmianida Ainis; Mustofa, Fauzi; Latifah, Umi (YASIN, 2023)
This qualitative descriptive research examines the discussion of learning that specializes in the field of tahfidz Al-Qur'an. Learning is a process of teaching and learning activities carried out by students with teachers and learning resources in a learning environment, strategy, or application in an environment. In another sense, that the learning system includes parts that are related to one another. Strategy, materials, objectives, procedures, and assessments are some of these components. In using and deciding on the development of media, techniques, tactics, and strategies to be used in the teaching and learning process, the teacher must pay attention to the four learning components. At MI Integrated Al-Ma'shum, the learning method is devoted to Tahfidz Al-Quran, so this article discusses four methods, namely the talqin, talaqqi, ziyadah, murojjaah methods.